FORMATION OF THINKING OPERATIONS OF SCHOOLCHILDREN PSYCHOLOGICAL FEATURES - Djolımbetova, M.M. (SCIENCE and SOCIETY, 2026)
The state presents information on the psychological characteristics of schoolchildren's mental development, the development of mental processes and freedom of thought, as well as the study and analysis of the thought process in various literature.
Keywords: psychology of schoolchildren; development of mental operations; free thinking; psychological influence of social factors on the development of the cognitive process